The social construction of sexuaity - Seidman, Steven (Contemporary Societies, 2010)
In The Social Construction of Sexuality, Steven Seidman investigates the political and social consequences of privileging certain sexual practices and identities while stigmatizing others. Addressing a range of topics from gay and lesbian identities to sex work, he delves into issues of social control that inform popular beliefs and moral standards. The Second Edition of The Social Construction of Sexuality features a new part that focuses on sexuality and social institutions.